Integrin α11β1 is expressed in breast cancer stroma and associates with aggressive tumor phenotypes. (3rd December 2019) - Smeland, Hilde Ytre‐Hauge; Askeland, Cecilie; Wik, Elisabeth; Knutsvik, Gøril; Molven, Anders; Edelmann, Reidunn J; Reed, Rolf K; Warren, David J; Gullberg, Donald; Stuhr, Linda; Akslen, Lars A
Abstract: Cancer‐associated fibroblasts are essential modifiers of the tumor microenvironment. The collagen‐binding integrin α11β1 has been proposed to be upregulated in a pro‐tumorigenic subtype of cancer‐associated fibroblasts. Here, we analyzed the expression and clinical relevance of integrin α11β1 in a large breast cancer series using a novel antibody against the human integrin α11 chain. Several novel monoclonal antibodies against the integrin α11 subunit were tested for use on formalin‐fixed paraffin‐embedded tissues, and Ab 210F4B6A4 was eventually selected to investigate the immunohistochemical expression in 392 breast cancers using whole sections. mRNA data from METABRIC and co‐expression patterns of integrin α11 in relation to αSMA and cytokeratin‐14 were also investigated. Integrin α11 was expressed to varying degrees in spindle‐shaped cells in the stroma of 99% of invasive breast carcinomas. Integrin α11 co‐localized with αSMA in stromal cells, and with αSMA and cytokeratin‐14 in breast myoepithelium. High stromal integrin α11 expression (66% of cases) was associated with aggressive breast cancer features such as high histologic grade, increased tumor cell proliferation, ER negativity, HER2 positivity, and triple‐negative phenotype, but was not associated with breast cancer specific survival at protein or mRNA levels. In conclusion, high stromal integrin α11 expression was associated with aggressive breast cancer phenotypes.